Anxiety, pandemic‐related stress and resilience among physicians during the COVID‐19 pandemic. Issue 10 (12th August 2020) - Mosheva, Mariela; Hertz‐Palmor, Nimrod; Dorman Ilan, Shirel; Matalon, Noam; Pessach, Itai M.; Afek, Arnon; Ziv, Amitai; Kreiss, Yitshak; Gross, Raz; Gothelf, Doron
Abstract: Background: Physicians play a crucial frontline role in the COVID‐19 pandemic, which may involve high levels of anxiety. We aimed to investigate the association between pandemic‐related stress factors (PRSF) and anxiety and to evaluate the potential effect of resilience on anxiety among physicians. Methods: A self‐report digital survey was completed by 1106 Israeli physicians (564 males and 542 females) during the COVID‐19 outbreak. Anxiety was measured by the 8‐item version of the Patient‐Reported Outcomes Measurement Information System. Resilience was evaluated by the 10‐item Connor–Davidson Resilience Scale. Stress was assessed using a PRSF inventory. Results: Physicians reported high levels of anxiety with a mean score of 59.20 ± 7.95. We found an inverse association between resilience and anxiety. Four salient PRSF (mental exhaustion, anxiety about being infected, anxiety infecting family members, and sleep difficulties) positively associated with anxiety scores. Conclusions: Our study identified specific PRSF including workload burden and fear of infection that are associated with increased anxiety and resilience that is associated with reduced anxiety among physicians.